Mediation of motivation on communication, equity and influence organizational commitment to employee performance - I Nyoman Rasmen Adi; Ni Made Anggun Dhanu Ariesandi; Made Mulyadi; Luh Gede Elvina Adi Saputri (Jurnal Mantik, 2023)
The purpose of this research is to analyze empirically the mediation of motivation on the effect of communication, fairness and organizational commitment on employee performance. For this reason, perception data were collected from 100 employees. Employees are asked to fill out a questionnaire that has been tested for validity and reliability. Data were analyzed by SEM assisted by Smart PLSversion 4.0.9.5. Research findscommunication and organizational justice have been able to increase motivation significantly. However, high organizational commitment has not been able to increase motivation significantly. Communication and motivation by the leadership of the company has been able to significantly improve employee performance. On the other hand, organizational justice and organizational commitment have not significantly increased employee performance. In addition, it was also found that motivation does not mediate the effect of communication and organizational justice on employee performance. Meanwhile, motivation is the full mediation effect of organizational commitment on employee performance. The existence of motivation is more dominantly influenced by organizational commitment while the existence of employee performance is dominantly influenced by work motivation